Parapentaneura bentogomensis Stur, Fittkau et Serrano (Diptera, Chironomidae, Tanypodinae) taken in Southeastern, Brazil: additional characters and modified generic diagnosis - Oliveira, Caroline Silva Neubern de; Fonseca-Gessner, Alaíde Aparecida; Navarro-Silva, Mário Antônio (Biota Neotropica, 2010)
The genus Parapentaneura was established in 2006 and is composed of a single species, Parapentaneura bentogomensis, originally from Mato Grosso State. This species was collected in São Paulo State and is thus redescribed. The specimens from both localities were compared, adding new characters to the description of the species and emending the genus diagnosis. The new record increases considerably the geographical distribution of Parapentaneura.